(untitled) (Eurasian Journal of Ecology, 2018)
The article contains the results of the study of the restoration of the vegetation cover of the pastures of the Kurtinsky rural district. The authors carried out corrective mapping, the course of vegetative cover restoration was studied by comparing different data. The article is based on the results of research carried out on the territory of the Kurtinsky district in 2015 and analysis of the dynamics of vegetation cover. The geobotanical map of the scale 1: 200000 of the Kurta district of Almaty region of 1991, based on the information collected by P.E.Ertayeva and I.N. Voznesenskaya in 1979-1991, was based on the restoration process of the vegetation cover of this region. During the research, additions and corrections to the geobotanical map and cartographic method were introduced, the research objective of which was the contours of the map. During the study, a route plan was organized on motor vehicles. The contours necessary for the shape of the route and the topographic survey were taken into account. According to the results of the study, the data on the corrected cartography of the studied territory of the Aulsky district were filled on the form. In addition, a comparative analysis was carried out with the results of studies carried out in 1982 by A.P. Popova and in 2009, I.R. Mirzazanov. A brief survey of the state of the area in recent years was made and a group of Russian geobotanists, such as IR Mirzadinov, conducted research in the framework of the state programs of the Ministry of Education and Science of the Republic of Kazakhstan in the period 2003, 2006, 2009. In general, during the period of gaining independence in 24 years, the state of this region has improved noticeably. In 2015-2016, amendments were introduced, selected in 1982 by A.P. Popova contours of the Aul district of the Kurtinsky district №42, №49, №54, №56, №143, №60, -№61, №44, №52, №144, №140, №58, №53, №47, № 48, No. 139 No. 145. The experimental value of the research work of the vegetative cover of the Aulsky district of the Kurtinsky district was the methods corresponding to pasture lands and arid territory in order to improve the ecosphere and the state of the region as a whole. Experimental significance of the study is the rational use of the ecosystem resources of the Aulskaya district of the Kurtinsky district according to its arid territory and the vegetation cover of the area. Key words: desertification, route, corrective mapping, vegetation dynamics, regenerative processes